Synthesis of fully biobased semi-aromatic furan polyamides with high performance through facile green synthesis process. (5th January 2022) - Xie, Shuang; Yang, Jiacao; Wang, Xiaojun; Yang, Jie
Graphical abstract: Highlights: Facile green synthesis process. Fully biobased semi-aromatic furan polyamides with high performance. The weight-average molecular weight, glass transition temperature and initial decomposition temperature of PA10F produced are up to 62500 g/mol, 103 °C and 401 °C, respectively. The mechanical properties of PA10F prepared are outstanding with the maximum tensile strength of about 54.46 MPa, elongation at break of about 138.60%, and tensile modulus of about 1454 MPa. Abstract: Biobased polymers hold the promise of addressing climate change and biodiversity loss due to deriving from renewable carbon. Dimethyl furan-2, 5-dicarboxylate as a biobased monomer is potential alternative of terephthalic acid and has been widely used to produce biobased polyesters or polyamides. In this study, excellent performance of poly(decamethylene furanamide) (PA10F) was synthesized via bulk polymerization with 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD) as catalyst. For PA10F produced at 200 °C as well as 0.05 MPa, weight-average molecular weight, glass transition temperature ( Tg ) and initial decomposition temperature ( Td-5% ) were up to 62500 g/mol, 103 °C and 401 °C, respectively. Furthermore, the mechanical properties were also outstanding with the tensile strength of about  52.12 MPa, elongation at break of about 68.78%, and tensile modulus of about 1636 MPa. According to the result of X-ray diffraction analysis, the PA10F was amorphous.